Effect of Fangxia-Dihuang Decoction on doxorubicin-induced cognitive impairment in breast cancer animal model - Wang, Xuan; Sun, Qiqi; Li, Jianrong; Lai, Baoyong; Pei, Xiaohua; Chen, Nana (Frontiers in Oncology, 2025)
ObjectiveBased on the murine model, this study explored the efficacy of Fangxia-Dihuang Decoction (FXDH) in interfering with cognitive impairment induced by doxorubicin (DOX) after chemotherapy for breast cancer.MethodsBuild 4T1 breast cancer xenograft tumor model in Balb/c mice, intraperitoneal injection of DOX (5mg/kg) once a week, build the model of DOX induced chemotherapy related cognitive impairment (CRCI), and the administration lasted for three weeks. From the first week, while DOX was given, FXDH was given high, medium and low doses by gavage every day. Conduct Y-maze and Novel object recognition (NOR) tests, detect inflammatory factors and oxidative stress-related indicators in serum and hippocampus, observe neuroinflammation and neurodegenerative changes through immunofluorescence and Nissl staining. Observation of heart and liver injury through blood routine and cardiac Hematoxylin-Eosin(HE)Staining.ResultsAdministration of FXDH significantly improved cognitive impairment in mice. FXDH reduced the levels of pro-inflammatory cytokines IL-6, IL-12p70, and TNF-α (P<0.05), and increased the levels of anti-inflammatory cytokines IL-10 and IL-4 (P<0.05). FXDH increased the levels of GSH, GSH-PX, SOD, and CAT in serum and hippocampus (P<0.05), and decreased the level of MDA (P<0.05). The results of Nissl staining and immunofluorescence staining showed that FXDH improved the neurodegenerative lesions caused by DOX and the neuroinflammatory response in the hippocampus (P<0.05). The intermediate dose group of FXDH showed better efficacy. The results of blood routine and cardiac HE staining showed that compared with the 4T1 group, the serum ALT, AST, CK, LDH, and CKMB in DOX group mice were significantly increased (P<0.05). After FXDH administration, all indicators in mice were decreased, but there was no statistical difference. FXDH improved the disordered arrangement of myocardial cells, uneven cytoplasmic staining, and loose and disordered arrangement of myocardial fibers caused by DOX.ConclusionIn the animal model, FXDH has the effect of anti-cognitive impairment after chemotherapy for breast cancer, and can improve the DOX induced learning, memory and cognitive impairment in mice. FXDH can reverse DOX induced neuroinflammation by improving the neurodegenerative changes caused by DOX, reducing pro-inflammatory cytokine levels in mouse serum and hippocampus, increasing anti-inflammatory cytokine levels, and reducing oxidative stress response.